Mạng tính toán và ứng dụng - Kiếm, Hoàng Văn; Nhơn, Đỗ Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper we propose a model that can be used for representing knowledge. It is called a computational net. We also discuss some on a computational net, and prove the algorithms used to solve the problems. Algorithms have been implemented and tested carefully in various applications. In this paper we bring out two application examples in  geometry and in chemistry.